2022
DOI: 10.1039/d1fo04305f
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium animalis subsp. lactis XLTG11 improves antibiotic-related diarrhea by alleviating inflammation, enhancing intestinal barrier function and regulating intestinal flora

Abstract: Antibiotic-associated diarrhea (AAD) is a common side effect during antibiotic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…For example, VSL#3 (Cheng et al, 2020), which was considered as medical food, contains eight live strains of bacteria, including four strains of Lactobacillus, three strains of Bifidobacterium and one strain of Streptococcus. B. lactis XLTG11 was isolated from the intestine of healthy infants with excellent probiotic properties, which can regulate the immunity system, alleviate inflammation, enhance intestinal barrier and regulate gut microbiota (Weiwei et al, 2022;Xu et al, 2022). It has been suggested that Lactobacillus plantarum P8 can survive in the host intestine, improve the community structure of intestinal flora, reduce the adhesion, infestation and colonization of harmful bacteria, promote the growth of beneficial bacteria, enhance the barrier function of intestinal flora, and have a positive regulatory effect on humoral immunity, cellular immunity and immunity of intestine-related lymphoid tissues (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, VSL#3 (Cheng et al, 2020), which was considered as medical food, contains eight live strains of bacteria, including four strains of Lactobacillus, three strains of Bifidobacterium and one strain of Streptococcus. B. lactis XLTG11 was isolated from the intestine of healthy infants with excellent probiotic properties, which can regulate the immunity system, alleviate inflammation, enhance intestinal barrier and regulate gut microbiota (Weiwei et al, 2022;Xu et al, 2022). It has been suggested that Lactobacillus plantarum P8 can survive in the host intestine, improve the community structure of intestinal flora, reduce the adhesion, infestation and colonization of harmful bacteria, promote the growth of beneficial bacteria, enhance the barrier function of intestinal flora, and have a positive regulatory effect on humoral immunity, cellular immunity and immunity of intestine-related lymphoid tissues (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the B. lactis XLTG11, L. casei Zhang and L. plantarum P8 could enhance immune function in mice, respectively (Wang et al, 2013(Wang et al, , 2014Fu et al, 2020;Weiwei et al, 2022;Xu et al, 2022). However, studies on enhancing effects of complex probiotic preparations containing B. lactis XLTG11, L. casei Zhang and L. plantarum P8 have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…AAD is often accompanied by systemic inflammation, characterized by a significant increase in proinflammatory factors and a significant decrease in anti-inflammatory factors [ 53 ]. Changes in proinflammatory cytokines include tumor necrosis factor and interleukins, both of which play a primary role in communicating with immune cells and reflect inflammatory infiltration in the host [ 54 ]. Therefore, the levels of inflammatory cytokines are evaluated in AAD, including TNF and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…known to be effective in improving diarrhea and IBS-D. For example, L. plantarum 299v is known to be effective in controlling abdominal bloating [ 18 ], and Bifidobacterium animalis spp. XLTG11 is known to be effective in controlling antibiotic-related diarrhea [ 19 ]. Unfortunately, there has been no direct comparative study of whether combinations of probiotics are more effective than a single strain, and conclusions vary from disease to disease and from strain to strain.…”
Section: Discussionmentioning
confidence: 99%